The impact of social environment and educational level on public knowledge and attitudes towards organ donation: Can we do better? - Grbić, K.; Alić, J.; Lepara, O.; Omić, S.; Heljić, J.; Krupić, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. For many patients with end-stage disease, organ transplant often provides the only chance for survival. Organ donation (OD) is affected by legislation, cultural and ethnic background, and knowledge and attitudes play a crucial role in promoting that concept. The present study aimed to assess differences in education level, perception, and willingness towards OD among Bosnian immigrants living in Sweden and respondents living in Bosnia and Herzegovina.Study design. We performed a quantitative cross-sectional study using a self-administered questionnaire among 204 participants.Methods. The questionnaire provided demographic characteristics, information about opinions, awareness, and knowledge on the donation process and religious approach to the subject, willingness to donate/receive organs, and possession of a donor card.Results. All respondents supported OD, regardless of their education level. Only 2% of university-educated individuals from Bosnia and Herzegovina claimed to be donor card owners (p